The Validity and Students Response toward Coordination System Teaching Material Oriented Guided Inquiry - Jan Hendriek Nunaki; Yelsi Patiung; Novri Youla Kandowangko; Elya Nusantari; Insar Damopolii (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Learning in the 21st-century class expects teachers to apply learning that invites students to conduct investigations. Guided inquiry learning is an example of learning that can train students' investigative abilities. This study aimed to analyze the validity and response of students on the used of coordination system teaching materials oriented guided inquiry. This research was part of research and development research that adapts the 4D model. The research subjects were 17 students of XI Grade SMA YPK Oikoumene Manokwari. Three experts and three practitioners were used for the validation process and a focus group discussion (FGD). Validation results showed that the coordination system teaching material oriented guided inquiry was valid and can be used for testing in the classroom. The response of students in the small group trial showed that learning could improve their motivation, comprehension, skill and interested in biology teaching. Their response is excellent. It can be concluded that the coordination system for teaching material oriented guided inquiry can be using for the next stage of testing to see its effectiveness. The effectiveness of learning in the next trial will be carried out in the future.